THE SPECIFICATION OF A MENU-SELECT INTERACTIVE SYSTEM BASED ON CSP THEORY - Enikeev, Arslan; Mohammed, Mahfoodh Bilal Ahmed (European Scientific Journal, ESJ, 2014)
This paper presents a model for the creation of software systems using the example of a menu-select interaction system based on Communication Sequential Process (CSP) theory. This theory enables the specification and analysis of various patterns of communication between processes. The model includes the specifications of commonly used processes such as ‘stoppable’, ‘resettable’, ‘backtrackable’ and ‘coroutine’. Implementation of the model has been carried out on the basis of LISP language and it has been approved in a series of tests.